Literature Review: The Effect of Maternal Age on the Incidence of Ectopic Pregnancy - Asmara, Intan; Wahyu Kurniasih, Kristining; Titik Nuryanti, Yuli; Triani, Triani; Pramesti, Dian; Windayanti, Hapsari (Proceedings of Conference on Health Universitas Ngudi Waluyo, 2026)
Ectopic pregnancy is a life-threatening obstetric emergency and remains a major cause of maternal morbidity and mortality during the first trimester of pregnancy. Maternal age has been recognized as one of the potential risk factors; however, findings across studies remain inconsistent. This literature review aimed to synthesize current evidence regarding the association between maternal age and the occurrence of ectopic pregnancy. A literature review was conducted using articles published between 2021 and 2026. Literature searches were performed in Google Scholar, GARUDA, PubMed, and relevant international journals using the keywords “ectopic pregnancy,” “extrauterine pregnancy,” “tubal pregnancy,” “maternal age,” “advanced maternal age,” “adolescent pregnancy,” “risk factor,” “predictor,” and “determinant”, combined with Boolean operators (AND/OR). The inclusion criteria were original research articles, full-text availability, publication between 2021 and 2026, studies investigating ectopic pregnancy, its risk factors, diagnosis, management, or patient outcomes, and articles published in English or Indonesian. Exclusion criteria included duplicate publications, editorials, opinion papers, letters to the editor, conference abstracts, inaccessible full-text articles, and studies unrelated to the review objectives. Following title and abstract screening and full-text assessment, seven studies that met the eligibility criteria were included in the qualitative synthesis. Five of the seven included studies reported a statistically significant association between maternal age and ectopic pregnancy (p < 0.05), indicating that women younger than 20 years and older than 35 years were at greater risk. Two studies found no statistically significant association. Variations in study design, sample size, population characteristics, statistical analyses, and adjustment for confounding factors may explain these inconsistent findings. Additional factors associated with ectopic pregnancy included parity, previous abortion, infertility, previous ectopic pregnancy, pelvic inflammatory disease, smoking, assisted reproductive technology, and a history of tubal surgery. Current evidence suggests that maternal age is an important risk factor for ectopic pregnancy, particularly among women younger than 20 years and older than 35 years. However, methodological heterogeneity across studies warrants cautious interpretation. Further high-quality studies with standardized methodologies are needed to strengthen the available evidence